AKULTURASI ISLAM DAN BUDAYA LOKAL: ANALISIS NILAI-NILAI FILOSOFIS TRADISI PENYAMBUTAN KEPULANGAN HAJI DAN RITUAL TASYAKURAN - Mohammad Rifai; Moh Farid Ridlo Rofii (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The tradition of welcoming returning Hajj pilgrims and the accompanying thanksgiving rituals in Indonesia are not merely sociological phenomena of geographical relocation; rather, they represent a cultural space laden with the dialectic of acculturation between Islamic orthodoxy and local traditions. This study aims to radically dissect the varieties of cultural nuances, the models of religious-cultural hybridization, and the philosophical values embedded within the Hajj homecoming celebrations and thanksgiving rituals (walimatun naqi’ah). Employing a descriptive qualitative method enhanced by a comparative ethnographic approach, this study analyzes three primary regional focuses as descriptive loci, namely the welcoming traditions in Java, Madura (asajere), and Bugis-Makassar (mappatoppo). The findings conclude that this tradition embodies a harmonious integration manifested into three substantive philosophical values: (1) A theological-spiritual transformation from individual piety toward becoming agents of social piety; (2) The recreation and reinforcement of communal social capital to reduce polarization; and (3) The existence of cultural expressions of gratitude that manifest the theory of the indigenization of Islam (Pribumisasi Islam) in the Indonesian Archipelago. This research implies a strengthening of the literature in the anthropology of religion regarding the flexibility of theological Islamic doctrines when adapting to local Nusantara cosmologies without uprooting the essence of tawhid (monotheism).